Question and Answers Forum

All Questions      Topic List

None Questions

Previous in All Question      Next in All Question      

Previous in None      Next in None      

Question Number 56471 by harish 12@g last updated on 17/Mar/19

Answered by tanmay.chaudhury50@gmail.com last updated on 17/Mar/19

∫_0 ^π ((xdx)/(a^2 cos^2 x+b^2 sin^2 x))dx=I  I=∫_0 ^π (((π−x))/(a^2 cos^2 (π−x)+b^2 sin^2 (π−x)))dx  =∫_0 ^π ((π−x)/(a^2 cos^2 x+b^2 sin^2 x))dx  2I=∫_0 ^π ((π−x+x)/(a^2 cos^2 x+b^2 sin^2 x))dx  ((2I)/π)=∫_0 ^π (dx/(cos^2 x(a^2 +b^2 tan^2 x)))dx  ((2I)/π)=∫_0 ^π ((sec^2 xdx)/(a^2 +b^2 tan^2 x))dx  ((2I)/π)=(1/b^2 )∫_0 ^π ((sec^2 xdx)/(((a/b))^2 +tan^2 x))dx  now  ∫_0 ^(2a) f(x)dx=2∫_0 ^a f(x)dx  when f(2a−x)=f(x)  ((2I)/π)=(2/b^2 )∫_0 ^(π/2) ((sec^2 xdx)/(((a/b))^2 +tan^2 x))dx  tanx=(a/b)tanp    sec^2 xdx=(a/b)sec^2 pdp  ((b^2 I)/π)=∫_0 ^(π/2) (((a/b)sec^2 p)/(((a^2 /b^2 ))(1+tan^2 p)))dp  ((b^2 I)/π)=(b/a)∫_0 ^(π/2) dp  ((abI)/π)=∣p∣_0 ^(π/2)   ((abI)/π)=(π/2)  so I=(π^2 /(2ab))  proved

0πxdxa2cos2x+b2sin2xdx=II=0π(πx)a2cos2(πx)+b2sin2(πx)dx=0ππxa2cos2x+b2sin2xdx2I=0ππx+xa2cos2x+b2sin2xdx2Iπ=0πdxcos2x(a2+b2tan2x)dx2Iπ=0πsec2xdxa2+b2tan2xdx2Iπ=1b20πsec2xdx(ab)2+tan2xdxnow02af(x)dx=20af(x)dxwhenf(2ax)=f(x)2Iπ=2b20π2sec2xdx(ab)2+tan2xdxtanx=abtanpsec2xdx=absec2pdpb2Iπ=0π2absec2p(a2b2)(1+tan2p)dpb2Iπ=ba0π2dpabIπ=∣p0π2abIπ=π2soI=π22abproved

Terms of Service

Privacy Policy

Contact: info@tinkutara.com